ANALISIS KESALAHAN SISWA SMA DALAM MENYELESAIKAN SOAL TRIGONOMETRI BERBASIS KEMAMPUAN PENALARAN MENGGUNAKAN KATEGORI KESALAHAN WATSON - Gustiani Rahayu (Departement of Mathematics Education, 2019)
This study aims to determine the reasoning abilities of high school students and describe the types of student errors in solving trigonometry problems. The form of research used is descriptive qualitative research, with the object of research being students of class X Language at SMA Albidayah. The selected students are students who have studied trigonometric material. The students who were sampled were 24 students. With the selected sample is a sample that has high, moderate and low mathematical abilities seen from academic achievement. In this study, students were given tests with instruments in the form of questions consisting of 4 items based on students' mathematical reasoning. Based on the results of this study, it can be concluded that the results of the test analysis of students' mathematical reasoning abilities in trigonometry material are said to be sufficient, namely by the percentage of 43.739%. The type of error based on the Watson category is carried out by students with high, medium, and low ability, namely incorrect data / incorrect data, improper procedures, incorrect data, and other than seven errors / others.